Peningkatan Kemandirian Belajar Mahasiswa Prodi Matematika Fakultas Sains dan Teknologi UIN Sumatera Utara Melalui Model Pembelajaran project Based Learning - Siregar, R. Maisaroh Rezyekiyah (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2022)
This study aims to see the magnitude of in increase in the self-regulated learning of students by using a project based learning model. This study method was quantitative. The sample in this study were taken using purposive sampling technique. The research instruments used were (1) test essay test to classify students based on ability level (2) questionnaire to see student self regulated learning.The instrument was be avowed to have met the requirements of content validity, as well as the reliability coefficient. The magnitude of the increase in the self regulated learning ability from before to after receiving learning with this learning model can be seen by calculating the normalized gain (g). Based on the results of research on increasing student self-regulated learning has increased based on the average value of normalized gain > 0.7 with high criteria.The result of this studyÂ was recommended for teachers or other users who want to increase the student self-regulated learning.